2006
DOI: 10.1021/bm050772t
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Confinement and α-Helix Persistence Length in Poly(γ-benzyl-l-glutamate)-b-poly(dimethyl siloxane)-b-poly(γ-benzyl-l-glutamate) Triblock Copolymers

Abstract: The structure and the associated dynamics of a series of poly(gamma-benzyl-L-glutamate)-b-poly(dimethyl siloxane)-b-poly(gamma-benzyl-L-glutamate) (PBLG-b-PDMS-b-PBLG) triblock copolymers were investigated using small- and wide-angle X-ray scattering, NMR, transmission electron microscopy, and dielectric spectroscopy, respectively. The structural analysis revealed phase separation in the case of the longer blocks with defected alpha-helical segments embedded within the block copolymer nanodomains. The alpha-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…Using the bending stiffness, we estimate the persistence length of the AH protein (at T = 300 K) to approximately be 5.5 nm. This result agrees somewhat with experimental studies that found a persistence length of a AH structure on the order of 1-2 nm [Papadopoulos et al 2006]. The reason for this disagreement could, for example, be rate effects.…”
Section: The Sequence Of the Protein Considered Here Is Gly Ser Asn Gsupporting
confidence: 91%
“…Using the bending stiffness, we estimate the persistence length of the AH protein (at T = 300 K) to approximately be 5.5 nm. This result agrees somewhat with experimental studies that found a persistence length of a AH structure on the order of 1-2 nm [Papadopoulos et al 2006]. The reason for this disagreement could, for example, be rate effects.…”
Section: The Sequence Of the Protein Considered Here Is Gly Ser Asn Gsupporting
confidence: 91%
“…26 Furthermore, the computed lamellar microstructure should be expected based on simple volume fraction rules, 1 but has not been experimentally observed. This deviation from experiment is believed to arise due to three factors: (1) monodisperse chain lengths, (2) strong segregation brought about by the repulsive PDMS/PBLG interactions, and (3) short spatial length scale.…”
Section: Resultsmentioning
confidence: 93%
“…It is hence useful to put our finding of the highly flexible nature of the Smc2-Smc4 coiled coils (L P ∼4 nm) into perspective. While a single alpha helix is very flexible (L P ∼1 nm; Papadopoulos et al., 2006 ), coiled coils are in general significantly more stiff. Theoretically, the persistence length of a coiled coil formed by two alpha helixes has been predicted to be as high as 200 nm ( Yogurtcu et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%